Composition of essential and non-essential elements in tissues and body fluids of healthy subjects and patients with colorectal polyps. (5th May 2009) - Alimonti, Alessandro; Bocca, Beatrice; Mattei, Daniela; Lamazza, Antonietta; Fiori, Enrico; Masi, Ercole; Pino, Anna; Forte, Giovanni
This study was devoted to the quantification of 21 metals (Al, Ba, Ca, Cd, Co, Cr, Cs, Cu, Fe, Hg, Li, Mg, Mn, Mo, Ni, Pb, Se, Sn, Sr, V and Zn) in the colorectal tissue of 52 healthy subjects, 31 patients with polyps and 21 post-operated patients, and in blood, serum and urine of all subjects. Tissues of healthy subjects had a content of metals similar to those of post-operated patients and to normal tissues adjacent to the polyp. The polyps had concentrations of Al, Ba, Ca, Cd, Co, Cr, Cu, Hg, Mo, Ni, Sr and V significantly lower and of Fe and Se significantly higher respect to normal tissues. Polypotic patients had higher serum Cr, Cu and Pb and lower urinary Mo levels than healthy subjects, whereas blood showed no difference. Results highlighted metal-specific differences both at tissue and systemic level probably caused by the early stage of colorectal cancer.